Penafsiran Tentang Interaksi Sosial dengan Non Muslim - Nur Azizah; Nurhadipah Nurhadipah; Adrian Wilza; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses the concept of social interaction in Islam, particularly in the context of relationships between Muslims and non-Muslims. Islam teaches values of ukhuwah (brotherhood), tolerance, and justice in interactions with fellow human beings, both within Muslim communities and with those of different beliefs. The central principle taught in Islam is that there is no compulsion in religion (la ikraha fid-din), as religion is a personal choice and belief that cannot be forced. In the context of dialogue or debate with non-Muslims, Islam emphasizes the importance of good manners, politeness, and gentleness, so that debates or discussions can lead to the mutual discovery of truth without insulting or belittling others. Thabathabai’s interpretation explains that debating with non-Muslims should be done constructively, without containing any errors, flaws, or insults. However, debating with the unjust, who close themselves off from the truth, is considered unproductive and will only worsen the situation. This article also highlights that differences in religion, culture, and beliefs should be an opportunity for mutual understanding and cooperation in creating peace and well-being together. Islam teaches the importance of maintaining harmonious relationships with fellow humans, whether in social, political, or religious contexts, while respecting freedom of belief and personal integrity